SPOKEN TEXT FEATURES OF THE CONVERSATION IN TV TALK SHOW OF TALK INDONESIA - Mutmainnah, Hidyatul; Sutopo, Djoko (Language Circle: Journal of Language and Literature, 2016)
The aims of this study were to describe how the participants show spontaneity features, to describe how the participants show interpersonal function, to describe the information flow among the participants and to describe how the participants achieve coherence and relevance in the conversation of TV talk show of Talk Indonesia. This study applied descriptive qualitative research. The data were taken from two videos of talk show entitle Talk Indonesia that was broadcasted in Metro TV. The data were analyzed by using conversation analysis. Conversation analysis was used to analyze or investigate the structure and process of social interaction between humans. It was a kind of discourse analysis method that focuses primarily on talk (Cameron, 2001:48). The result of this study showed that there were some various spoken features found in the conversation of talk show for instance spontaneity, Interpersonality, interactivity and coherence features. Each of features had some aspects. The finding showed that among participants showed the spoken text features variously. Although some overlaps and interruptions occurred in the conversation, the talk show could still run well.